Studies on the effect of brown rice and maize flour on the quality of bread (Journal of the Bangladesh Agricultural University, 2012)
Breads were prepared with various combinations of maize, brown rice and wheat flours in the basic formulation of   bread. The baking properties and chemical composition of bread were evaluated and analysed, respectively. The   bread volume decreased, where as bread weight and moisture content increased with the increasing level of maize   and brown rice flour. The crumb and crust colour of breads were improved with addition of 8% maize and 8% brown   rice flour in bread formulation. The protein content and other nutrients of breads were increased by addition of maize   and brown rice flours. The effects of various levels of yeast, sugar, fat, improver and salt on the quality of breads   prepared with maize and brown rice flour were evaluated. Bread quality in respects of bread volume and crumb   texture were improved by using 2.5% yeast, 5% sugar, 5% fat and 0.6% improver. The analysis of bread containing   added 8% maize and 8% brown rice flours showed protein 9.76%, fat 4.10%, ash 2.10%, crude fibre 5.16%, sugar   2.26% and total carbohydrates 46.91%. Bread having 8% maize and 8% brown rice flour had most acceptable   flavour, texture, colour and overall acceptability when compared with other bread with maize and brown rice flour.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.11044   J. Bangladesh Agril. Univ. 9(2): 297304, 2011